Effects of public ownership on corporate performance: empirical evidence from Turkish manufacturing industry - Saraç, Mehmet. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
This dissertation provides an empirical analysis of the changes in operating performance and certain financial characteristics of firms as they make the transition from private to public ownership through initial public offerings (IPOs). The expectations are tested on a sample of 81 Turkish manufacturing firms that went public between 1990 through 1998 inclusive. Eight-year-data of each firm around IPO year are included in the sample. First, operating return on assets, sales, capital expenditures, leverage and cost of financing of each firm in the sample are examined throughout an eight-year-window. Statistical analyses are performed to see if there are significant differences before and after IPOs. Then, the possible causes are investigated to explain the changes. Change in certain stock market indicators is also considered.The findings show that firms exhibit a substantial decline in post-IPO operating performance, assets turnover and capital expenditures on assets. There is an increase in leverage and decrease in cost of borrowing. Those firms retaining higher proportion of capital inside seem to exhibit less decrease in performance after IPO. Those firms that underprice their stocks at IPO seem to show higher decrease in post-IPO performance. These two findings, however, lack sufficient statistical significance. High-pre-IPO operating performance and market buoyancy around IPO date seem to lead investors to develop optimistic assessments of earnings growth.
Keywords: Industrial policy -- Turkey.